PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP MINAT BELI GEPREK ABU AHDA - Rahmadani, Nopi; Wirangga, Rezi; Zarna, Abael Diva; Sanjaya, Vicky F (Journal for Management Student (JFMS), 2023)
Marketing strategies in business must pay attention to providing customer satisfaction. The aim of this research is to determine whether price and product quality influence purchasing interest. This research is a quantitative research, the research used 90 respondents who were consumers of Abu Ahda Geprek Chicken. The data obtained was processed using a questionnaire. In this research, the indirect effect that is formed is weakening. The data collection technique is primary data or data taken directly from respondents through questionnaires. In this study, the results obtained were that price had a positive but not significant effect on buying interest, and product quality had a positive and significant effect on buying interest.